Structural performance of FRP-RC compression members wrapped with FRP composites. (October 2020) - Raza, Ali; Ali, Babar; Asad Nawaz, Muhammad; Ahmed, Ibrar
Abstract: The literature is deficient for the theoretical predictions of the axial loading capacity of Fiber Reinforced Polymers (FRP) reinforced concrete-filled FRP tube (CFFT) columns. The present study aims to propose new models for predicting the axial loading capacity of FRP reinforced CFFT columns. Two types of FRP bars were used in this work: one is glass fiber reinforced polymer (GFRP) bars and the second is carbon fiber reinforced polymer (CFRP) bars. Two different databases were developed from the previous experimental works. One of the databases consisted of experimental results of 500 FRP-confined concrete compression members and the second database consisted of experimental results of 279 FRP-reinforced concrete columns. An empirical model was proposed for the axial load-carrying capacity of FRP-reinforced CFFT columns using these databases. For the comparative study, a nonlinear finite element model (FEM) was simulated for FRP-reinforced CFFT columns using concrete damaged plastic (CDP) model. A detailed parametric study was also performed using the proposed FEM to investigate the effect of various parameters of studied specimens. A close agreement was observed between the proposed empirical and numerical models.